1966
DOI: 10.1080/00039896.1966.10664421
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior, Illness Behavior, and Sick-Role Behavior

Abstract: THE FIRST part of this presentation began with definitions of the three kinds of health-related behavior. Health behavior is any activity undertaken by a person believing himself to be healthy, for the purpose of preventing disease or detecting it in an asymptomatic stage. Illness behavior is any activity, undertaken by a person who feels ill, to define the state of his health and to discover a suitable remedy. Sick-role behavior is the activity undertaken, for the purpose of getting well, by those who conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
4

Year Published

1972
1972
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(113 citation statements)
references
References 68 publications
2
105
0
4
Order By: Relevance
“…Preventive behaviors can be defined as behaviors expected for the prevention or early detection of diseases like cervical cancer at an asymptomatic stage [40]. These behaviors are not equally revealed among social groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventive behaviors can be defined as behaviors expected for the prevention or early detection of diseases like cervical cancer at an asymptomatic stage [40]. These behaviors are not equally revealed among social groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have demonstrated that women who are in social class 5 (those most at risk of developing cervical cancer) are least likely to perform cervical cancer screening. Studies have also revealed that women who are not interested in screening may be older, have a lower salary, or come from a lower socioeconomic class than those who undergo a Pap test [40, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence from Spain confirms a significant relationship between socioeconomic determinants and mental illness, including a rise in somatoform disorders [36], among others. On a similar trajectory alluding to the theory behind somatoform disorders [37,38], Kentikelenis et al [16] reported that in Greece people view their health as ‘bad' or ‘very bad'. The same study reports on increased heroin use and associated physical morbidity.…”
Section: The Effects Of Financial Crises On Mental Healthmentioning
confidence: 99%
“…2 The need to maintain positive health behavior has become a subject matter of exploration by social and behavioral scientists during the last few decades. Kasl and Cobb 3 have conceptualized three categories of health behavior -'preventive health behavior' which implies any action taken by a healthy individual for the purpose of preventing or detecting illness; 'illness behavior' which implies that an individual, who perceives himself to be ill, takes up remedial measure to get healthy and 'Sick-role behavior' which refers to an action taken by an individual who considers himself to be ill, for the purpose of getting well.…”
Section: Introductionmentioning
confidence: 99%